Meningkatkan Perkecambahan Biji Kelor (Moringa oleifera Lam.) Tersimpan Menggunakan Asam Giberelat: Improving the Germination of Kelor (Moringa oleifera Lam.) Seeds Stored Using Gibberellic Acid - Bambang Budi Santoso (LPPM Universitas Mataram, 2022)
Gibberelin (Gibberellic acid) is a plant hormone that is responsible for the seed germination process. Germination is the process by which an inactive embryo grows and eventually forms a seedling and subsequently produces a seedling. A total of 50 seeds of Moringa (Moringa oleifera Lam.) which have been stored for 12 months and 24 months were soaked in different concentrations of Gibberellin solution (0 mg/L; 2.5 mg/L, 5.0 mg/L, 7.5 mg/L, dan 10.0 mg/L) for 24 hours and then sown in a bath soil-sand-husk charcoal (1:1:1 v/v) germination. Since 10 days after planting the seeds, observations and calculations were made on the number of seeds that germinated, the number of abnormal germinations, and the number of days when 50 percent of the seeds germinated. The results showed that the number of seeds and the speed of seed germination were proportional to the concentration of Gibberellins. Seeds treated with high concentration of Gibberellin (9 mg/L) had the highest number of germination seeds compared to seeds with lower concentration of Gibberellin. Without giving Gibberellins from the outside, Moringa seeds that have been worn out (stored 1-2 years) were not able to germinate properly.